Enhancing research and innovation visibility through PIID 2023 / Nor Azliza Akbar … [et al.] - Akbar, Nor Azliza; Ibrahim, Anas; Abdul Hamid, Mohd Samsudin; Mahmood, Ainorkhillah; Ahmad, Hazrina (UiTM Global @ Office of International Affairs, 2024)
The Penang International Invention, Innovation and Design (PIID 2023) Competition was held from 16 to 18 May 2023 at Dewan Besar, Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, Malaysia. This event was organised by the Research Management Unit in collaboration with the Centre for Civil Engineering Studies, UiTM Pulau Pinang Branch to serve as a platform for students, academicians, industries, and professionals to highlight innovation, invention and design in their respective fields related to science, technology, engineering, mathematics and social sciences. It is also in line with the government’s policy to encourage research activities in Malaysia and to meet the Sustainable Development Goals.